2021
DOI: 10.1590/1984-70332021v21sa24
|View full text |Cite
|
Sign up to set email alerts
|

Spray-induced gene silencing: an innovative strategy for plant trait improvement and disease control

Abstract: Modern plant breeding is still a time-consuming and costly process, even with the most advanced technologies such as gene editing. Hence, there is an urgent need to develop alternative means for plant trait manipulation and plant protection. RNA interference (RNAi) is a conserved cellular mechanism mediated by naturally occurring double-stranded RNA (dsRNA) and small RNAs (sRNAs) that can target mRNAs for destruction or transcript reduction. Here, we review the potential of technology based on RNAi, called spr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 63 publications
0
11
0
Order By: Relevance
“…In addition, it has been revealed that during the infection process, plant sRNAs can be transferred to pathogens in order to silence genes critical for their growth or virulence; similarly, pathogens can enhance their virulence by transferring to sRNA targeting host defense genes [ 133 ]. Altogether, this sRNA-based communication process, first identified in plant-fungi interactions [ 139 ], has been called “Bidirectional cross-kingdom RNAi” [ 131 , 132 , 139 , 140 , 141 ] and its discovery has represented a milestone for inspiring new strategies for crops protection [ 131 , 132 , 140 , 141 ]. Recent investigations on the mechanisms of sRNAs uptake by fungal pathogens from plant cells indicate that sRNA molecules are delivered from plants through exosomes or extracellular vesicles that are absorbed by fungal cells through endocytic fusion with the cell membrane [ 142 , 143 , 144 , 145 ].…”
Section: Innovative and Sustainable Approachesmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, it has been revealed that during the infection process, plant sRNAs can be transferred to pathogens in order to silence genes critical for their growth or virulence; similarly, pathogens can enhance their virulence by transferring to sRNA targeting host defense genes [ 133 ]. Altogether, this sRNA-based communication process, first identified in plant-fungi interactions [ 139 ], has been called “Bidirectional cross-kingdom RNAi” [ 131 , 132 , 139 , 140 , 141 ] and its discovery has represented a milestone for inspiring new strategies for crops protection [ 131 , 132 , 140 , 141 ]. Recent investigations on the mechanisms of sRNAs uptake by fungal pathogens from plant cells indicate that sRNA molecules are delivered from plants through exosomes or extracellular vesicles that are absorbed by fungal cells through endocytic fusion with the cell membrane [ 142 , 143 , 144 , 145 ].…”
Section: Innovative and Sustainable Approachesmentioning
confidence: 99%
“…These sRNAs specifically target pathogen key genes arresting the infection processes and conferring a stable protection of the host [ 139 , 152 , 153 , 154 ]. Alternatively, sRNAs can be designed to silence plant genes encoding susceptibility factors, i.e., proteins preventing pathogen recognition and the host defense response [ 141 , 155 ].…”
Section: Innovative and Sustainable Approachesmentioning
confidence: 99%
“…One non-transgenic approach with much of the functionality of HIGS is to use spray-induced gene silencing (SIGS), wherein dsRNA sprays are used as a pesticide to target and knock down the expression of important pathogen genes. The persistence of dsRNAs sprayed on leaf surfaces is a major challenge and depends strongly on the formulation, but in some cases the dsRNAs can retain biological activity for over 4 weeks [ 173 , 174 ]. The technology has shown some promise for insect pests as well as viral, fungal, and oomycete pathogens, although research with fungal pathogens is still in the preliminary stages and dsRNA uptake varies among fungi [ 173 , 174 , 175 ].…”
Section: Potential For Transgenic Banana Plants Resistant To Black Si...mentioning
confidence: 99%
“…The persistence of dsRNAs sprayed on leaf surfaces is a major challenge and depends strongly on the formulation, but in some cases the dsRNAs can retain biological activity for over 4 weeks [ 173 , 174 ]. The technology has shown some promise for insect pests as well as viral, fungal, and oomycete pathogens, although research with fungal pathogens is still in the preliminary stages and dsRNA uptake varies among fungi [ 173 , 174 , 175 ].…”
Section: Potential For Transgenic Banana Plants Resistant To Black Si...mentioning
confidence: 99%
“…In addition to their endogenous role, specific sRNAs can travel between interacting species and regulate the function of recipient cells by hijacking their RNAi machinery (19,20). Furthermore, RNAi has recently been exploited to control plant pathogens by exogenous application of sRNAs targeting genes in pathogens essential for disease development by a process called spray-induced gene silencing (21)(22)(23) .…”
Section: Introductionmentioning
confidence: 99%